Monocyte to high-density lipoprotein ratio based prognostic nomogram for patients following allogeneic vascular replacement pancreaticoduodenectomy - Ye, Xiao-Wen; Wang, Zu-Yu; Shao, Yun-Xia; Tang, Ying-Chun; Dong, Xiong-Jun; Zhu, Ya-Ning (Frontiers in Genetics, 2024)
Background Preoperative immune-inflammatory condition influencing the metabolism of malignancies. We sought to investigate the prognostic value of a novel immune-inflammatory metabolic marker, the monocyte-to-high-density lipoprotein ratio (MHR), in patients with locally advanced pancreatic cancer. Methods A retrospective analysis was conducted on the clinical data of 118 patients with locally advanced pancreatic cancer and obstructive jaundice who underwent allogeneic vascular replacement pancreaticoduodenectomy in our hospital from Apr. 2011 to Dec. 2023. To assess the predictive capacity of immune-inflammatory metabolic marker, we utilized the area under the receiver operating characteristic curve (AUC-ROC) and assessed the predictive potential of MHR in forecasting outcomes through both univariate and multivariate Cox proportional hazard analyses. Results The area under AUC for MHR in predicting 1-year postoperative survival was 0.714, with an optimal cutoff value of 1.184, yielding a sensitivity of 78.9% and specificity of 66.2%. Based on this cutoff value, patients were divided into a low MHR group (MHR ≤1.184, n = 61) and a high MHR group (MHR >1.184, n = 57). The median survival times for the low and high MHR groups were 27.0 months and 12.0 months, respectively (χ2 = 30.575, p < 0.001), and the median DFS were 18.0 months and 8.0 months, respectively (χ2 = 26.330, p < 0.001). Univariate and multivariate analyses indicated that preoperative MHR, preoperative creatinine, operation duration, and TNM stage were independent predictors of postoperative mortality, while preoperative MHR, preoperative creatinine, and TNM stage were independent predictors of postoperative recurrence risk. Conclusion MHR, as an independent immune-inflammatory metabolic predictor of OS and DFS in patients with advanced PC after pancreaticoduodenectomy. Early monitoring and reduction of MHR may be of great significance in improving prognosis.